Penguatan Manajemen Strategis Bisnis Online Generasi Z dalam Perspektif Bimbingan Karir - Pratama, Fidya Arie; Nakhma’Ussolikhah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Guidance and counseling are in a transition period from conventional-based services to internet-based services. The presence of technology is the biggest challenge for today's individuals, who have used internet-based service media. Such individuals are called generation Z born around 1995 to 2010. The demands of technological developments are the biggest obstacles for BK teachers born in generations X and Y. The purpose of this study is to find the communication experience of Generation Z in building an online business through social media. The study used a qualitative method with data collection using observation and interview techniques. The subjects of the study were individuals born in 1998, 2000, 2004. The activities of individuals born in generation Z are very dependent on smartphones can provide a sense of comfort, security, happiness and peace, this is felt by individuals when accessing several applications available on smartphones. The use of smartphones makes it easy for individuals to surf the internet without limits. This affects the shift in paradigms and attitudes of individuals both consciously and unconsciously. The results of the study show that individuals born in generation Z can feel the freedom and ease in developing an online business career without having to need a place and capital, especially for beginners in online business as resellers.